Partial trisomy 16q21➔qter due to an unbalanced segregation of a maternally inherited balanced translocation 46,XX,t(15;16)(p13;q21): a case report and review of literature - R. Mishra; C. S. Paththinige; N. D. Sirisena; S. Nanayakkara; U. G. I. U. Kariyawasam; V. H. W. Dissanayake (BMC, 2018)
Abstract Background Partial trisomy is often the result of an unbalanced segregation of a parental balanced translocation. Partial trisomy16q is characterized by a common, yet non-specific group of craniofacial dysmorphic features, and systemic malformations with limited post-natal survival. Most of the cases of partial trisomy 16q described in the scientific literature have reported only one, or less frequently two cardiac defects in the affected babies. Herein, we report a case of partial trisomy 16q21➔qter with multiple and complex cardiac defects that have not previously been reported in association with this condition. Case presentation We report the phenotypic and cytogenetic features of a Sri Lankan female infant with partial trisomy 16q21➔qter. The baby had a triangular face with downslanting eyes, low set ears and a cleft palate. Systemic abnormalities included multiple cardiac defects, namely double outlet right ventricle, ostium secundum atrial septal defect, mild pulmonary stenosis, small patent ductus arteriosus, and bilateral superior vena cavae. An anteriorly placed anus was also observed. The proband was trisomic for 16q21➔qter chromosomal region with a karyotype, 46,XX,der(15)t(15;16)(p13;q21)mat. The chromosomal anomaly was the result of an unbalanced segregation of a maternal balanced translocation; 46,XX,t(15;16)(p13;q21). Partial trisomy 16q was established by fluorescence in-situ hybridization analysis. Conclusions The craniofacial dysmorphic features and the presence of cardiac and anorectal malformation in the proband are consistent with the phenotypic spectrum of partial trisomy 16q reported in the scientific literature. More proximal breakpoints in chromosome 16q are known to be associated with multiple cardiac abnormalities and poor long-term survival of affected cases. This report presents a unique case with multiple, complex cardiac defects that have not previously been described in association with a distal breakpoint in 16q. These findings have important diagnostic and prognostic implications.